Platon o starości i ludziach starych - Zmorzanka, Anna Z. (Vox Patrum, 2011)
The article presents Plato’s views on topic of the old age and aged people. There were talked the following topics over: (1) Plato’s terminology of the old age on the background of vocabulary arisen to first half of fourth age; (2) periodization of older age presented in Laws; (3) theory on topic of the aging presented in Timaeus; (4) how mean should lives through his own old age – for example the old man Cephalus; (5) view on topic of the elderly’s role in society; (6) laws of the elderly and project of social care in vision of ideal state. There was said in conclusion, that Plato was only one ancient author, who extensively appeared the problems of old age as well, but philosophical anthropology was that things, which joined different voices in cohesive theory.